Criminal Liability for the Perpetrator of Wife and Child Abandonment in the Household - Findianti, Sinta Annabella; Sopacua, Margie Gladies; Muammar, Muammar (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: Criminal liability is a legal process that ensures that every individual who commits a criminal act must be responsible for his or her actions, in this case the neglect of wife and children, criminal liability serves to provide a deterrent effect to the perpetrator and protect the rights of victims who have been harmed.Purposes of the Research: This study aims to analyze criminal liability for perpetrators of wives and children neglect in the household with a case study of Court Decision Number 45/Pid.Sus/2020/PN Psb.Methods of the Research: The research methods used are normative research, legislative approaches, primary and secondary legal materials and material collection procedures using literature studies. The approaches used are: statute approach, conceptual approach, and casus approach. Legal material tracing techniques using document study techniques, and study analysis using qualitative analysis.Findings of the Research: The results of the study show that criminal liability to the perpetrators of wives and children abandonment in the Court Decision Number 45/Pid.Sus/2020/PN. PSB, namely the defendant in being sentenced to prison for 3 (three) months, besides that the defendant will also improve his behavior and be responsible as the head of household for his family in the future,